Influence of seasonality and production method on the antibacterial activity of propolis - Souza, Edison Antonio de [UNESP]; Inoue, Hemily Tiemi [UNESP]; Fernandes Júnior, Ary [UNESP]; Veiga, Nabor [UNESP]; Orsi, Ricardo De Oliveira [UNESP] (Universidade Estadual de Maringa, 2014)
The antibacterial activity of propolis produced throughout the year by different methods of collection ('intelligent' collector of propolis - ICP; plastic screen - PC; conventional scraping - CS) on Staphylococcos aureus and Escherichia coli is investigated. Fifteen beehives (five per collector) of Africanized Apis mellifera were used. Monthly produced propolis, with the same collection technique, was mixed for the preparation of the extract. The ethanol extract of propolis (EEP) was prepared at the ratio of 30% (30 g of propolis, completing the volume for 100 mL with ethanol 70%). Two microorganisms, a positive bacterium Gram Staphylococcus aureus and a negative bacterium Gram Escherichia coli, through the methodology of diffusion in agar, were used for the biological activity evaluation of EEP. Results show that propolis presented antibacterial activity, affected by seasonality and by collecting method.

O objetivo deste estudo foi investigar a atividade antibacteriana da própolis produzida ao longo do ano por diferentes métodos de coleta (coletor de própolis 'inteligente' - CPI, tela plástica - TP e raspagem convencional - RC) sobre Staphylococcos aureus e Escherichia coli. Foram utilizadas 15 colmeias de Apis mellifera africanizadas. Para o preparo do extrato, foi misturada a própolis produzida mensalmente pela mesma técnica de coleta. O EAP foi preparado na proporção de 30% (30 g de própolis completando o volume para 100 mL com etanol 70%). Para avaliação da atividade biológica do EAP, foram usados dois micro-organismos: uma bactéria gram positivia Staphylococcus aureus e uma gram negativa Escherichia coli, por meio da metodologia de difusão em ágar. Os resultados mostraram que a própolis apresenta atividade antibacteriana, sendo esta influenciada pela sazonalidade e método de colheita utilizado.
Influência da sazonalidade e método de produção na atividade antibacteriana da própolis
Keywords: Apiculture; Biological properties; Quality; Bacteria; Apicultura; Atividade biológica; Qualidade; Bactéria